Measuring the effect of institutional change on gender inequality in the labour market. (March 2015) - Dieckhoff, Martina; Gash, Vanessa; Steiber, Nadia
Abstract: This article examines the differential impact of labour market institutions on women and men. It carries out longitudinal analyses using repeat cross-sectional data from the EU Labour Force Survey 1992–2007 as well as time series data that measure institutional change over the same period. The results contribute to the literature on gendered employment, adding important insights into the impact of labour market institutions over and above family policies that have been the focus of most prior studies on the topic. We find differential effects of institutional change on male and female outcome. Our findings challenge the neo-classical literature on the topic. While our results suggest that men benefit more clearly than women from increases in employment protection, we do not find support for the neo-classical assertion that strong trade unions decrease female employment. Instead, increasing union strength is shown to have beneficial effects for both men's and women's likelihood of being employed on the standard employment contract. Furthermore, in line with other researchers, we find that rising levels of in kind state support to families improve women's employment opportunities.